Glycodeline-A, sFlt-1, PlGF Combined as Predictor Markers of First Trimester Pregnancy Loss in Iraqi Women (Medico Legal Update, 2021)
Objective: evaluate the serum level of Glycodeline-A, sFlt-1, PlGF combined with ?hCGas predictormarkers of first trimester pregnancy loss in Iraqi women .Method: A case-contol study, carried out from April 2019 to March 2020 and included 85 women, 40 ofthem as patients which have abortion at the first trimester and 45 of them as healthy control which haven,t any complication at the same time of gestation, investigations included serum measurements of ?hCG,Glycodeline-A, sFlt-1, PlGF By Method ELISA.Results: Serum Niveaus?hCG, sFlt-1 Was major higher in healthy controls than in patients, while serumlevel of Glycodeline-A, PlGF was significantly lower in healthy control than in patients, and there is nosignificant correlation among each of age with other parameters, and there is no significant correlationamong each of gest.age with Glycodeline-A and sFlt-1, while there is significant correlation among each ofges.age with ?hCG and PlGF P